2015
DOI: 10.1021/acsami.5b05838
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Quantum Dots-based Photoluminescent Sensor: A Multifunctional Composite for Pesticide Detection

Abstract: Due to their size and difficulty to obtain, cost/effective biological or synthetic receptors (e.g., antibodies or aptamers, respectively), organic toxic compounds (e.g., less than 1 kDa) are generally challenging to detect using simple platforms such as biosensors. This study reports on the synthesis and characterization of a novel multifunctional composite material, magnetic silica beads/graphene quantum dots/molecularly imprinted polypyrrole (mSGP). mSGP is engineered to specifically and effectively capture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(57 citation statements)
references
References 44 publications
0
57
0
Order By: Relevance
“…In particular, innovative carbon-based nanomaterials such as graphene quantum dots (GQDs) and graphene oxide quantum dots (GOQDs) have attracted much interest as stable, nontoxic, photoluminescent nanomaterials with possible applications in chemical and biological sensors, drug delivery, bio-imaging and energy conversion [7][8][9][10][11][12][13]. The physical origin of the photoluminescence (PL) from these carbonbased nanoparticles is still quite controversial and different mechanisms have been suggested, possibly acting together, mainly based on quantum confinement in sp 2 domains with a strong influence from edge and oxygen-containing functional groups [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, innovative carbon-based nanomaterials such as graphene quantum dots (GQDs) and graphene oxide quantum dots (GOQDs) have attracted much interest as stable, nontoxic, photoluminescent nanomaterials with possible applications in chemical and biological sensors, drug delivery, bio-imaging and energy conversion [7][8][9][10][11][12][13]. The physical origin of the photoluminescence (PL) from these carbonbased nanoparticles is still quite controversial and different mechanisms have been suggested, possibly acting together, mainly based on quantum confinement in sp 2 domains with a strong influence from edge and oxygen-containing functional groups [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Such a facile and cost-effective biosensor was developed to interrogate the presence of organophosphate pesticides in food, water and the environment. Another GQD-sensor for the determination of pesticides was constructed by Zor et al As shown in Figure 5B [157]. Herein, a multifunctional nanocomposite, i.e., magnetic silica beads/GQDs/molecularly imprinted polypyrrole (mSGP), was synthesized for specifically capturing and signaling small molecules owing to the synergism offered by this composite in terms of optical, chemical and magnetic features along with molecular imprinting of tributyltin, a genotoxic substance that can cause endocrine disruptions.…”
Section: Photoluminescence-based Gqd-sensorsmentioning
confidence: 99%
“…Magnetic GQDs embedded molecularly imprinted polypyrrole (mSGP) were designed to specifically and effectively capture, pre-concentrate and detect analytes due to the synergy among chemical, magnetic and molecular imprinting properties with the fluorescence properties of GQDs, which are quenched upon analyte recognition. 124 This multifunctional material enables a rapid, simple and sensitive platform for small molecules detection even in complex media such as seawater without any sample treatment.…”
Section: Chemical Sensorsmentioning
confidence: 99%